(untitled) - Vietnam (The Socialist Republic of); Government (Hà Nội, 2004)
The strate for sustainable development in Vietnam is composed of five parts: sustainable development Vietnam's anticipated path, priority economic areas for sustainable development, priority social areas for sustainable development, priority areas in natural resource utilisation, environmental protection and pollution control for sustainable development and sustainable development implementation arrangements.
Keywords: Sustainable development,Phát triển bền vững; Vietnam,Việt Nam